ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN MICROSOFT (STUDI KASUS DI KABUPATEN REMBANG) - Lukiarti, Ming Ming (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
In marketing, there is no doubt that customer loyalty is essential. Marketers will always try tokeep their customers in long period or even forever if it is possible. Therefore, this researchtries to examine the factors that influence the customer loyalty. These factors are perceivedrisk, switching costs and corporate image as a moderating variable between switching costsand customer loyalty. The necessary data was obtained through interviews using questionnairesto 100 respondents. The obtained data then analyzed by using the technique of Partial LeastSquare (PLS-SEM).The results of statistical test by using Partial Least Square (PLS-SEM) showed that, theperceived risk has a positive effect on switching cost, switching cost has a positive effect oncustomer loyalty and corporate image did not moderate the relationship between switchingcosts and customer loyalty. Based on the results, a managerial implications can be drawn,namely loyalty enhanced by increasing switching costs and perceived risk. This is done byalways creating a system performance that is easier to operate and easy to understand throughcreating operating systems is no more difficult than the previous editions and provide multitaskingcapabilities that have larger capacity. In addition , it should provide better security systemsthat are not easily infected by virus or cyber criminals hacked, give the perception that ismore expensive and difficult to move to another operating system by means of improvingcustomer satisfaction and provide good services (performance) within the operating system,simplify and make it cheaper for the installation of new programs and increase customerengagement (eg: forming a community joint branding with the mobile phone company or othercomputer company) to provide added value for Microsoft customers.